Efeitos da presença de macrófitas aquáticas nos macroinvertebrados de córregos tropicais - Fonseca, Daniel Gonçalves da (Universidade Federal de São Carlos, 2011)
The riparian forest deforestation by pasture activities allows greater solar incidence on the streams bed. The high input of light favours the development of aquatic macrophytes, which also contributing with the high primary production rate and are important substrate for aquatic organisms. This substrate generates stability subunities and complex microhabitats which are used as refugee, places and feeding source and interfere in the trophic relations in the streams. Benthic macroinvertebrates can be affected in several ways by fish (predators) through direct effects (feeding) or indirect effects (predation risk, bio-perturbation, trophic links). However, the complexity offered by the macrophytes can influence the trophic interactions between fish and the macroinvertebrates, decreasing the predation pressure and allowing the coexistence among these organisms. The objective of this study was to evaluate the macrophyte influence on the aquatic communities. With the purpose of facilitate the understanding, the study was divided in two chapters: (1) It compared the macroinvertebrate assemblages present in sites with or without macrophytes in three different streams; (2) It evaluated the aquatic macrophyte effects on the colonization of macroinvertebrate communities and on the predation interaction between macroinvertebrates and fish, using an experiment with exclusion cages in two streams. The results allow a better understanding of the functional processes in the structure of the streams, providing knowledge about the human interaction effects on the functioning of these systems.
Keywords: Ecologia; Macrófitas aquáticas; Peixes; Comunidades; Communities; Aquatic macrophytes; Macroinvertebrates; Fishes; Predation; Pasture streams; CIENCIAS BIOLOGICAS::ECOLOGIA